The Leadership Importance in International Organization for Standardization (ISO) Implementation: A Literature Review - Riwayadi, Eko (PT FORMOSA CENDEKIA GLOBAL, 2024)
In the era of globalization doing business, organization always needs to be competitive, succeed and maintain sustainability as long as possible. Organization shall implement continual improvement in their excellent quality of management strategy to achieve their goals. Organization also needs to adapt to the international best practice. International Organization for Standardization or ISO is one of the best standard to be referred and implement their standard in the organization. In many cases implementation of ISO facing issues related to leadership commitment. Several research argued that leadership is not the main factor to be success in implementation of the ISO standard while other researcher argued that the leadership is playing very significant role to achieve ISO certification. This gap lead to this literature review research. Literature review shown that leadership is proven playing significant role to keep organization meeting the ISO requirement. This result imply to every organization to keep leadership to be number one priority to implement ISO or else the organization will face totally failure is implementing ISO Standard